PENGARUH PENERAPAN MARKETING SYARIAH, WOM DAN GAYA KEPEMIMPINAN KARISMATIK TERHADAP CITRA LEMBAGA YAYASAN PONDOK PESANTREN AL-KAHFI BANGKALAN MADURA - Dyatmika, Sutama Wisnu; Setioningtyas, Widhayani Puri; Mahrus, Mahrus (2021)
The purpose of this research is none other than to find out that the implementation of sharia marketing affects the image of the al-Kahfi Islamic boarding school foundation, then to find out that the Word of Mouth (WOM) affects the image of the al-Kahfi Islamic boarding school foundation, furthermore to determine the charismatic leadership style affects the image. Al-Kahfi Islamic Boarding School Foundation, Bangkalan Madura. by using quantitative research methods and data analysis using saturated sampling techniques with a population and a sample of 54 respondents. The research instrument used a questionnaire and this research was carried out at the Al-Kahfi Islamic Boarding School Foundation, Madura. The research results obtained through multiple linear regression analysis with partial t test and simultaneous F test, which has a significant value of 0.000 in the Islamic marketing variable and the WOM variable has a significance value of 0.002 then the charismatic leadership style variable has a value of 0.000 and finally the significance value the institutional image variable has a value of 0.000 with an F value of 45,952. this is in accordance with the hypothesis or provisional conjecture put forward by the researcher.